Aplikasi limbah panen padi dan pupuk kalium untuk meningkatkan hara kalium dan pertumbuhan serta produksi kedelai (Glycine max (L.) Merrill.) - Dwi Putriana Br Tambunan; Hamidah Hanum; Abdul Rauf (Jurnal Agroekoteknologi, 2015)
The research were to evaluate the effect of giving rice waste harvest and potassium fertilizer and its interaction to increasing potassium nutrient, the growth and the production of soybean (Glycine max (L.) Merill.). Already implementeded at gauze house and at laboratory Research and Technology of Agricultural Faculty of North Sumatera University, Medan from April to August 2014. The method used Factorial Randomized Complete Design with two factor and three replicatiosn. First factor is rice waste that is no giving rice waste (J0), straw compost 5 ton ha-1 (J1), straw charcoal 5 ton ha-1 (J2) and husk 5 ton ha-1 (J3) and the second factor is potassium fertilizer or Muriate of Potash (MOP) that is 0 kg ha-1 (K0), 50 kg ha-1 (K1), 100 kg ha-1 (K2), and 150 kg ha-1 (K3). The results showed that the rice waste increase K-exc and the highest by husk 5 ton ha-1 treatment. Potassium also increasing K-exc and the highest by 100 kg ha-1 treatment. Application of rice waste harvest and potassium fertilizer were not effected in soil pH, C-organic, K plant uptake, the growth, and the crop production.Keywords : straw compost, straw charcoal, husk, potassium fertilizer, soybean.